Contradições no processo de elaboração e monitoramento do Plano Municipal de Educação de São Carlos – SP(2005-2019): entre a democratização do planejamento e a participação outorgada - Gomes, Flávia Camila (2021)
This research aims in the State, Policy and Human Formation line of the Graduate Program in Education at UFSCar, analize as its object the process of elaborating and monitoring the Municipal Education Plan of São Carlos-SP, – PME, from 2005 to 2019. In the municipality of São Carlos (SP) the elaboration of the PME started in 2005, with the articulation of the Municipal Conferences taking PME as a central theme. In relation to the local with the national, we analyze the context of democratizing and neoliberal political projects in dispute in Brazil from the 1990s onwards. So, the objective of this research is to analyze the process of elaboration and monitoring of the SME of the municipality of São Carlos-SP in the period from 2005 to 2019, in face of the national political projects in dispute. To this end, specific objectives are to address the political projects in dispute in Brazil after 1990, focusing on the approaches taken on the concepts of participation, civil society and decentralization and their reflexes in the educational policy and policy of the period; rescue the history of construction of PNE in Brazil and its transformations (over time, in face of the projects in dispute) and the impact of the content of recent PNE in the process of elaboration and content of the SME of the municipality of São Carlos; systematize and analyze the content, the elaboration process and the monitoring process of the SME of the municipality of São Carlos, in the face of the political projects in dispute, identifying their possible reflexes on the local educational policy. It is a documentary research with bibliographic support. Throughout the systematization and analysis of local documentation, we identified the contradictions in the elaboration and monitoring process, in view of the inter-federative relations, as well as the conditions of participation of the established civil society. The local experience also showed contradictions in the modern liberal terms of citizenship initially adopted and the neoliberal deepening, as well as the dynamics between the democratic expansion and the instrumentalization of processes, including in the instance of institutionalization of the participation of civil society, the Municipal Council of Education. The absence of an effective collaboration regime, the emptying of financing conditions and the restriction of decentralization to the deconcentration of responsibilities are elements that make up the context of this process, and impose difficulties in overcoming strictly discursive and formal democratization.